2004
DOI: 10.1111/j.1525-1497.2004.30552.x
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of initiation of hospitalist clinician educators

Abstract: OBJECTIVE:Although hospitalists have been shown to improve both financial and educational outcomes, their ability to manage dual roles as clinicians and educators has been infrequently demonstrated, particularly in the community setting where large numbers of residents train. We evaluated the impact of hospitalists on financial and educational outcomes at a midsized community teaching hospital 1 year after implementation. DESIGN:Two hospitalist clinician educators ( HCEs) were hired to provide inpatient medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 17 publications
4
34
0
1
Order By: Relevance
“…3 Over the past ten years, an increasing number of studies have investigated the impact of hospitalists on outcomes, noting effects primarily in resource utilization and cost reduction, and less so in quality outcomes, patient satisfaction, and provider satisfaction. [14][15][16][17][18] Prior attempts to demonstrate an impact of overnight attending-level physicians on patient outcomes have been limited to the ICU, and revealed minimal impact. 19,20 To the best of our knowledge, our results are the first to describe patient-level outcomes following implementation of an OAH program for general medicine units.…”
Section: Discussionmentioning
confidence: 99%
“…3 Over the past ten years, an increasing number of studies have investigated the impact of hospitalists on outcomes, noting effects primarily in resource utilization and cost reduction, and less so in quality outcomes, patient satisfaction, and provider satisfaction. [14][15][16][17][18] Prior attempts to demonstrate an impact of overnight attending-level physicians on patient outcomes have been limited to the ICU, and revealed minimal impact. 19,20 To the best of our knowledge, our results are the first to describe patient-level outcomes following implementation of an OAH program for general medicine units.…”
Section: Discussionmentioning
confidence: 99%
“…En la medida que los hospitalistas reemplazan a sub-especialistas en el manejo de pacientes hospitalizados, se refuerza el concepto de manejo clínico general integral. Varios son los estudios que demuestran la preferencia de residentes por los hospitalistas en cuanto a satisfacción, calidad de las visitas, experiencia educativa, conocimientos del manejo intrahospitalario, discusiones de fisiopatología, énfasis en costo efectividad y feed-back (p < 0,05) [35][36][37] . Los estudiantes de medicina consideran que los hospitalistas proveen de una mejor experiencia educativa, de visitas más docentes y entusiastas, usan más la evidencia, modelan mejor los buenos modales, y tienen mayor presencia y compromiso con los pacientes (p ≤ 0,03) 38,39 .…”
Section: Docenciaunclassified
“…The authors found that hiring two hospitalist educators at their community-based teaching hospital led to decreased resource utilization and improved resident education when compared to having private physicians manage hospitalized patients. 7 Enhanced efficiency due to hospitalists has been demonstrated in several previous studies, in both community and academic settings. 8 The finding of an educational benefit for hospitalists in a community teaching hospital, however, is relatively new.…”
Section: Hospitalists In Teaching Hospitals: Opportunities But Not Wimentioning
confidence: 99%